Pendekatan Partisipatif Berbasis Kader dalam Meningkatkan Pengetahuan dan Keterampilan Pengelolaan Sampah Organik Rumah Tangga di Dusun Ngoto, Kabupaten Bantul - Dwimas Nurrohman Fadarsani; Putri Nazmah Abriwiyanti; Salsabila Dian Styowati; Tannia Larasaty; Heru Subaris Kasjono; Ibnu Rois (Poltekkes Kemenkes Yogyakarta, 2024)
Household organic waste remains an environmental health issue in Ngoto, Bantul, characterized by low levels of waste segregation and processing practices. This community service aimed to improve community knowledge and skills in managing organic waste through composting using a community empowerment approach. A participatory approach was implemented through four stages (L1–L4): problem identification, Community Self Survey (CSS), workshop-based cadre training, and community dissemination. The CSS involved ?50 households to identify priority problems. Training was conducted with 10 community cadres using pretest–posttest and skills observation. The CSS revealed that most households had not practiced proper waste segregation and organic waste processing. Training results showed an increase in knowledge, indicated by higher posttest scores compared to pretest scores. Participants also demonstrated the ability to perform composting independently. The dissemination stage indicated knowledge transfer to the broader community and the emergence of initial behavioral changes in organic waste management. A cadre-based community empowerment approach is effective in improving knowledge and skills in organic waste management and has the potential to promote sustainable behavioral change at the community level.